Observed amplification of the seasonal CO2 cycle at the Southern Ocean Time Series - Shadwick, Elizabeth H.; Wynn-Edwards, Cathryn A.; Matear, Richard J.; Jansen, Peter; Schulz, Eric; Sutton, Adrienne J. (Frontiers in Marine Science, 2023)
The Subantarctic Zone, the circumpolar region of the Southern Ocean between the Subtropical and Subantarctic fronts, plays an important role in air-sea CO2 exchange, the storage of anthropogenic CO2, and the ventilation of the lower thermocline. Here we use a time series from moored platforms deployed between 2011 and 2021 as part of the Southern Ocean Time Series (SOTS) observatory to investigate the seasonality and interannual variability of upper ocean hydrography and seawater CO2 partial pressure (pCO2). The region is a net sink for atmospheric CO2 over the nearly 10-year record, with trends revealing that the ocean pCO2 may be increasing slightly faster than the atmosphere, suggesting that oceanic as well as anthropogenic atmospheric forcing contributes to the decadal change, which includes a decline in pH on the order of 0.003 yr−1. The observations also show an amplification of the seasonal cycle in pCO2, potentially linked to changes in mixed layer depth and biological productivity.